Financial analysis of the South African life insurance sector: an empirical decomposition of Economic Value Added - Mangenge, Takalani (My University, 2015)
The main purpose of the study is to determine which value drivers of economic value added (EVA) are most important. That is, what are the main determinants of the overall company value? The three main questions raised in the study are: (1) How sensitive is total EVA to changes in each of the various value drivers? (2) Which of the value drivers are more important in managing economic value? (3) Is there a combination of these value drivers that best explain EVA as a group? The study, which adopts the Stewart (1991) definition of EVA, covers the life insurance sector in South Africa, specifically focusing on the following companies: Discovery Holdings, Liberty Holdings, MMI Holdings, Old Mutual plc, and Sanlam Ltd. It covers the period 2004-2014 and uses variance analysis and principal component analysis to identify the main drivers of EVA. Five main drivers of EVA were identified namely; underwriting, asset management, costs, opportunity cost and strategic investments.
Thesis (M.M. (Finance & Investment))--University of the Witwatersrand, Faculty of Commerce, Law and Management, Graduate School of Business Administration, 2015.
Keywords: Economic Value Added; Life Insurance; South Africa; Corporations; Finance